2022
DOI: 10.1038/s41420-021-00802-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel prognostic marker LINC00205 promotes tumorigenesis and metastasis by competitively suppressing miRNA-26a in gastric cancer

Abstract: Rapid proliferation and metastasis of gastric cancer (GC) resulted in a poor prognosis in the clinic. Previous studies elucidated that long non-coding RNA (LncRNA) LINC00205 was upregulated in various tumors and participated in tumor progression. The aim of our study was to investigate the regulating role of LINC00205 in tumorigenesis and metastasis of GC. Both public datasets and our data showed that the LINC00205 was highly expressed in GC tissues and several cell lines. Notably, GC patients with high level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Li et al found that LINC00205 targets the oncogene miR-185-5p as a potential therapeutic target in lung and gastric cancers. LINC00205 promoted the proliferation and migration of gastric cancer cells by inhibiting miR-26a [ 36 ]. Zhang et al suggested that LINC00205 targeting the high mobility group box 1 protein promoted the proliferation of neuroblastoma, which was correlated with OS [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al found that LINC00205 targets the oncogene miR-185-5p as a potential therapeutic target in lung and gastric cancers. LINC00205 promoted the proliferation and migration of gastric cancer cells by inhibiting miR-26a [ 36 ]. Zhang et al suggested that LINC00205 targeting the high mobility group box 1 protein promoted the proliferation of neuroblastoma, which was correlated with OS [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, LINC00592 was associated with patient prognosis and could target the cold shock domain-containing E1 protein, CDK6, miR-122-5p, and epoxide hydrolase 1, promoting the proliferation of hepatocellular carcinoma cells [30][31][32][33]. Li the proliferation and migration of gastric cancer cells by inhibiting miR-26a [36]. Zhang et al suggested that LINC00205 targeting the high mobility group box 1 protein promoted the proliferation of neuroblastoma, which was correlated with OS [34].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the biological functions of some of the identified lncRNAs (LINC00205, ZFPM2-AS1, LINC00942) have also been associated with other malignancies and might thus be nonspecific to HCC. [22][23][24][27][28][29][30]33,34 However, numerous other lncRNAs (AL139384.1, AL928654.1, AC145207.8, POLH-AS1, AC090772.3, AL603839.3, AC012073.1, AC099850.1, AC026401.3, AP001469.3, AL031985.3, SNHG10, SNHG21) lack corresponding basic studies to validate their prognostic roles in the development of HCC. Further studies are therefore needed to establish the associations of these identified lncRNAs with ferroptosis and their contribution to the regulation of HCC pathogenesis through ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…• enhances hepatoblastoma progression by regulating ROCK1 expression via sponging miR-154-3p through MAPK signaling 22 ; • promotes tumorigenesis and metastasis by competitively suppressing miRNA-26a in gastric cancer 23 ; • facilitates malignant phenotypes in lung cancer by recruiting FUS to stabilize CSDE1. 24 • activated by YY-1, facilitates the proliferation of HCC cells through YY1/miR-26a-5p/CDK6 25 ; • enhances tumorigenicity of HCC cells through modulating EPHX1 and inhibiting miR-184.…”
Section: Linc00205mentioning
confidence: 99%
“…The same characteristics also occurred in LINC00205. It may be used as a novel prognostic indicator of several cancers in multiple bioinformatics analyses, such as glioma [31], gastric cancer [32], and hepatocellular carcinoma [33][34][35]. Multiple lines of experimental evidence from basic research demonstrated the oncogenic role of LINC00205 in HCC, which may be beneficial for diagnosing and treating HCC [34,36].…”
Section: Discussionmentioning
confidence: 99%